On the interpretation of decay-associated fluorescence spectra in proteins - Ladokhin, A.S. (Біополімери і клітина, 2001)
Calculating decay-associated spectra (DAS) is a common mode of analyzing complex fluorescence decay in proteins. Unfortunately, these spectra are attributed almost exclusively to certain species in the population of macromolecules (retainers), often without sufficient evidence. An alternative explanation of decay heterogeneity, based on structural relaxation., was believed to require a negative DAS component. Here we demonstrate that dipolar relaxation of the indole molecule, lacking any rotameric forms, doesn't always result in negative pre-exponential amplitude. We conclude that the shape of DAS alone is not sufficient to differentiate among various causes of heterogeneity of tryptophan fluorescence decay in proteins. Расчет спектров, ассоциированных с затуханием (САЗ), является обычным путем анализа сложного затухания флюоресценции в белках. К сожалению, эти спектры почти исключительно относят к определенным видам в популяции молекул (ротамеров), часто без достаточных оснований Считалось, что альтернативное объяснение гетерогенности затухания, связанное со структурной релаксацией, требует отрицательной компоненты САЗ. В данной работе мы демонстрируем, что дипольная релаксация молекулы индола, лишенной каких-либо ротамерных форм, не всегда приводит к отрицательным при-экспоненциальным амплитудам. Мы делаем вывод о том, что форма САЗ сама по себе недостаточна, чтобы определить среди других причину гетерогенности затухания триптофановой флюоресценции в белках. Обрахунок спектрів, асоційованих із затуханням (САЗ), є звичайним шляхом аналізу складного затухання флюоресценції в білках. На жаль, ці спектри майже виключно відносять до певних видів у популяції молекул (ротамерів), часто без достатніх на те підстав. Вважалося, що альтернативне пояснення гетерогенності затухання, пов'язане зі структурною релаксацією, потребує негативної компоненти САЗ. У цій роботі ми демонструємо, що дипольна релаксація молекули індолу, позбавленої будь-яких ротамерних форм, не завжди призводить до негативних при-експоненціальних амплітуд. Ми робимо висновок стосовно того, що форма САЗ сама по собі не є достатньою, щоб вирізнити серед інших причину гетерогенності затухання триптофанової флюоресценції в білках.